alex-huth/GIMPM_SSA_Damage: GIMPM_SSA_Damage: Initial Release - Alex Huth (Zenodo, 2020)
This is the initial release of the Generalized Interpolation Material Point Method for the the Shallow Shelf Approximation of ice flow with Damage (GIMPM-SSA-Damage)